WHITHER INDIA? THEOLOGICAL CONCERNS - Kundukulam, Vincent (Asian Horizons, 2019)
Indian Theological Association (ITA) STATEMENT OF 42nd ITA MEETING NBCLC, Bengaluru, 28 April 2019 We, the members of the Indian Theological Association (ITA), gathered at National Biblical Catechetical and Liturgical Centre (NBCLC), Bengaluru for the Forty Second annual meeting cum conference from 25th to 28th April 2019 to deliberate on the theme, “Whither India? Theological Concerns”. In continuation with the previous conference of ITA on the theme “Challenges of Religious Nationalism in India Today”, the 42nd Annual Meeting went further in its reflections to give appropriate theological responses and deliberations to the contemporary context of the socio-political and cultural situation of India. Sixty-eight theologians from various parts of India reflected, discussed and deliberated on the present situation of India, our mother land, which is going through certain sociopolitical, religio-cultural and economic mutations that threaten the well-being of all citizens of our country whatever be their religious or ideological affiliations.